Professional Ethics on the Quality of Financial Reporting - Muhammad Wahyu Ramzy Ramadhan; Yanuar Ramadhan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to determine the extent of the impact of professional ethics on the quality of financial reporting, and how to apply it. This research is a literature review from various research sources. The results show that professional ethics has a significant relationship with the quality of financial reporting and is fundamental to the quality of an organization's financial statements. The application of quality financial reporting characters, high ethical commitment, and consistency play an important role in making quality financial reporting.